Common Variable Immunodeficiency and Non-Bacterial Thrombotic Endocarditis (Revista de Medicina Clinica, 2021)
Evans syndrome is a common autoimmune disease in patients with common variable immunodeficiency disease (CVID), while non-bacterial thrombotic endocarditis (NBTE) has not been described in association with CVID. We present the case of a 60-year-old man with CVID without complications associated with his disease; that after an episode of gastroenteritis of unknown etiology, he presented an Evans syndrome and a NBTE, complicated with a stroke of the right middle cerebral artery of cardioembolic cause. Given the lack of response to treatment with high doses of corticosteroids and intravenous immunoglobulin; two pulses of cyclophosphamide were administered and mycophenolate mofetil was subsequently started with resolution of the condition. We review the main autoimmune diseases associated with CVID as well as the thrombotic complications associated with treatment with intravenous immunoglobulins. We describe NBTE and its main associations as well as its possible pathophysiology. Finally, we conclude with the hypothesis that would relate the ETNB and the CVID in the context of an Evans syndrome.
Keywords: Common variable inmunodeficiency; nonbacterial thrombotic endocarditis; Evans Syndrome